A Critical Review on Nanowire‐Motors: Design, Mechanism and Applications. Issue 8 (26th May 2022) - Wang, Dashuang; Mukhtar, Aiman; Humayun, Muhammad; Wu, Kaiming; Du, Zhilan; Wang, Shushen; Zhang, Yuxin
Abstract: Nanowire‐motors (NW−Ms) are promoting the rapid development of emerging biomedicine and environmental governance, and are an important branch of micro‐nano motors in the development of nanotechnology. In recent years, huge research breakthroughs have been made in these fields in terms of the fascinating microstructure, conversion efficiency and practical applications of NW−Ms. This review article introduces the latest milestones in NW−Ms research, from production methods, driving mechanisms, control methods to targeted drug delivery, sewage detection, sensors and cell capture. The dynamics and physics of micro‐nano devices are reviewed, and finally the current challenges and future research directions in this field are discussed. This review further aims to provide certain guidance for the driving of NW−Ms to meet the urgent needs of emerging applications. Abstract : General overview of nanowire motors